STRATEGI BADAN PENGAWAS PEMILIHAN UMUM (BAWASLU) KOTA SURABAYA DALAM MENCEGAH PELANGGARAN KODE ETIK - Ongky Putra Noer Qolbu; Eni Rustianingsih (Journal Publicuho, 2025)
The purpose of this study is to describe the Strategy of the Election Supervisory Agency (Bawaslu) of Surabaya City in Preventing Violations of the Code of Ethics. Based on field observations regarding the leader's strategy in preventing violations of the code of ethics, it still experiences problems. This type of research uses a descriptive qualitative method. Data collection techniques through documentation, observation, and interviews. The determination of this research informant through purposive sampling consists of the Head of the Violation Prevention Division, who is responsible for preventing violations of the code of ethics. This study uses data collection techniques in the form of observation, in-depth interviews, and documentation of results. In this study also used two types of data sources, namely primary and secondary data. Data analysis techniques include data collection, data reduction, data presentation, and conclusion. The results of the study prove that the leader's strategy in preventing violations of the code of ethics has not been running as expected. In addition, violations were also committed by the Surabaya City Election Supervisory Agency in following up on existing violations. This is the main factor inhibiting the success of the Surabaya City Election Supervisory Agency (Bawaslu) Strategy in Preventing Violations of the Code of Ethics.